Pengembangan Umkm Dan Ekonomi Kreatif Di Kecamatan Kepanjenkidul Kota Blitar Melalui Seminar Legalitas Usaha, Digital Marketing Dan HAKI - Mu’tasim Billah; Nurcholish Majid; Mahesa Bachtiar Maulana; Arfad Syauqi Hikam Al Jonet; Munirotul Wahyuningsih; Gandhi Yoga Pratama; Galuh Deliana Putri Murdani; Desy Fitria Agustiyani (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
MSME development service activities as a way or solution to increase people's purchasing power, which in turn can cover up from the economic crisis situation. The implementation method used is by holding a seminar on entrepreneurship and creative economy entitled "The Urgency of Business Legality and Technology-Based Marketing for MSME Actors" which was held at the Kepanjenkidul District Office, Blitar City. The benefits of the entrepreneurship and creative economy seminar "The Urgency of Business Legality and Technology-Based Marketing for MSME Actors" are to provide learning and insight to MSMEs regarding Business Legality, Digital Marketing and Intellectual Property Rights. The main focus of this work program is business legality, digital marketing and intellectual property rights. Legality itself is a business license that is given to business actors to start and run their businesses and/or activities. Digital Marketing is an activity of a business strategy to develop business opportunities by expanding the market to increase sales targets. IPR is an effort to protect a work with Copyright so that there are no competitors who use our work for profit.